3D spatial data for building management case study - Sužiedelytė Visockienė, Jūratė; Tumelienė, Eglė; Kalinka, Maris; Eriņš, Ingars; Vaivode, Viktorija; Goldbergs, Lauris; Korna, Ieva; Smirnovs, Rolands; Gorovojs, Kirils (International Conference “Environmental Engineering”, 2023)
As the concept of the Metaverse develops, there is more and more discussion about the integration of digital data in various industries. Metaverse as a concept covers the use of various types of technologies and solutions in the virtual environment. This paper presents the application prototype of 3D spatial data in the building management cycle. New buildings and existing buildings contain different types of information: archive information, 3D geometric information, sensor information, etc. The building is not a stand-alone structure, but the plot of land on which it is located or the territory adjacent to it, which contains engineering communications and transport access possibilities, is attached to it. Building construction processes use BIM technologies and the 3D geometric models included in it, the application of which is not always effectively used after the building is built. The article discusses the acquisition, processing, and application of 3D data for the creation, monitoring and use of 3D geometrical models to analyse the life of the building. The article also discusses the issue of updating data during the life of the building and the application of the digital twin concept, applying future scenarios with the help of simulation. The aim of this work is to use 3D technologies, BIM and 3D models with building management.